Pengaruh Kualitas Kehidupan Kerja, Komunikasi Organisasi, Kepuasan Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai (Studi pada PNSD di Lingkungan Pemerintah Kota Bandung; Studi Pada PNSD Di Lingkungan Pemerintah Kota Bandung - Oktafien, Shinta; Yuniarsih, Tjutju (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2017)
The government of Bandung city had a responsibility to run administration, development of the government, and to provide excellent service for the community to create dignigfied, excellent, comfortable, and prosperous Bandung community. The success of the government in achieving performance targets was not balanced by the improvement of their employees’ performance. The aim of the study was to analyze the quality of work life, communication within the organization, work satisfaction and employees discipline within the government of Bandung, and the influence among these variables as well. The method of the study was explanatory survey. The population of this study was regional civil servants in Bandung city. Proportionate random sampling was used to 393 staff members of regional work units within the city of Bandung. The instrument was questionnaire, and data analysis used path analysis with the assist of a statistical package named SPSS 19.0. Based on the results of the study, it could be concluded that the employee performance will be built through quality of work life, effectiveness of organizational communication, job satisfaction, and work discipline. Recommendation are: Bandung City Government facilitates the development of employee skills, develops organizational communication more interactively, improves job satisfaction, improves work discipline, and optimizes the work time for each main task settlement